Plant Diversity of a Coffee-Based Agroforestry System in La Union, Philippines - Michael O. Barrientos; Aida DL. Escultor; Moesa C. Dela Cruz; Bonie A. Budeng; Hodnemer C. Bondad (Journal of Agroforestry and Environment, 2025)
Evaluating plant diversity in an agroforestry site is crucial for understanding the system, as vegetation is crucial for sustaining natural ecological processes and serves as a valuable resource for human consumption. This study aims to determine the tree species diversity of a coffee-based agroforestry system in a state university in La Union, Philippines. This research determined the species composition, density, frequency, dominance, importance value, and conservation status of the plant species, and also their richness, diversity, and evenness. A stratified sampling design was used in establishing quadrats. The study identified a total of 108 individuals across different vegetation layers, including 26 trees (16 species, 10 families), 38 saplings (12 species, 10 families), and 44 non-tree flora (14 species, 9 families), with Rain Tree (Samanea saman) and Coffee species (Coffea canephora and Coffea liberica) being the most dominant, highlighting a mixed native and introduced species composition within a coffee-based agroforestry system. The diversity is low (H’ = 1.79) for the saplings, while the non-tree and tree species are both categorized as moderate, with H’ of 2.15 and 2.65, respectively. However, there is a very high species evenness for tree species of (0.96) indicating extremely balanced community, while moderate evenness for saplings and non-tree species showed well-balanced community at a high evenness with a value of 0.72 and 0.83 respectively. This study offers valuable insights into the plant diversity of a managed coffee-based agroforestry system. Future studies may explore the implementation of strategies aimed at enhancing biodiversity within the coffee-based agroforestry system.